Technology Leadership, Teacher Motivation, and Pedagogical Competence in Senior High Schools of the Schools Division of Sultan Kudarat - Montero, Jicky (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationships among technology leadership, teacher motivation, and pedagogical competence in Senior High Schools of the Schools Division of Sultan Kudarat. It used a sequential explanatory mixed-methods design, with quantitative data gathered from 210 senior high school teachers through a validated survey questionnaire and qualitative insights obtained from open-ended responses. Findings revealed that technology leadership was perceived at a high level, particularly in vision-setting, planning, and professional development support, although budget allocation, internet reliability, and technical support remained areas of concern. Teacher motivation and pedagogical competence were both rated very high, showing that teachers were highly motivated to integrate technology and perceived themselves as competent in using digital tools, interactive lessons, feedback mechanisms, and ethical digital practices. Correlation analysis showed significant positive relationships among technology leadership, teacher motivation, and pedagogical competence. Regression and mediation analyses further indicated that technology leadership and teacher motivation significantly predicted pedagogical competence, with teacher motivation partially mediating the relationship between leadership and competence. The study concluded that strong technology leadership and teacher motivation support pedagogical competence, but infrastructure, preparation time, devices, and technical support must be strengthened to sustain effective technology integration.